2013
DOI: 10.1086/670217
|View full text |Cite
|
Sign up to set email alerts
|

An Environmental Disinfection Odyssey: Evaluation of Sequential Interventions to Improve Disinfection of Clostridium difficile Isolation Rooms

Abstract: OBJECTIVE. Effective disinfection of hospital rooms after discharge of patients with Clostridium difficile infection (CDI) is necessary to prevent transmission. We evaluated the impact of sequential cleaning and disinfection interventions by culturing high-touch surfaces in CDI rooms after cleaning. DESIGN. Prospective intervention. SETTING. A Veterans Affairs hospital. INTERVENTIONS. During a 21-month period, 3 sequential tiered interventions were implemented: (1) fluorescent markers to provide monitoring and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
111
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(117 citation statements)
references
References 21 publications
1
111
0
5
Order By: Relevance
“…The number of screened sites positive for C. difficile decreased by 14% (P ϭ 0.024), 48% (P Ͻ 0.001), and 89% (P ϭ 0.006) for interventions 1, 2, and 3, respectively, compared with prestudy levels. Positive cultures after disinfection were recovered from two-thirds of CDI rooms before the study began, whereas during periods 1, 2, and 3, the percentages of CDI rooms with positive cultures after disinfection fell by 57%, 35%, and 7%, respectively (68).…”
Section: Difficilementioning
confidence: 94%
See 1 more Smart Citation
“…The number of screened sites positive for C. difficile decreased by 14% (P ϭ 0.024), 48% (P Ͻ 0.001), and 89% (P ϭ 0.006) for interventions 1, 2, and 3, respectively, compared with prestudy levels. Positive cultures after disinfection were recovered from two-thirds of CDI rooms before the study began, whereas during periods 1, 2, and 3, the percentages of CDI rooms with positive cultures after disinfection fell by 57%, 35%, and 7%, respectively (68).…”
Section: Difficilementioning
confidence: 94%
“…A systematic cleaning and disinfection program was assessed by screening frequently touched surfaces for the presence of C. difficile in CDI rooms after cleaning (68). Three sequential interventions were introduced over a 21-month period: (i) fluorescent markers placed at key sites for the purposes of monitoring and feedback to cleaners, (ii) use of automated UV equipment for enhanced disinfection, and (iii) support from a designated team responsible for daily assessment of terminally cleaned CDI rooms.…”
Section: Difficilementioning
confidence: 99%
“…Hospital pathogens survive in the hospital environment until removed through some cleaning process but the best way to achieve this remains elusive [1,3,4]. Many studies have demonstrated persistent contamination following domestic attention, including high-risk hand-touch sites beside the patient [5][6][7][8][9]10 & ]. If a patient is admitted into a room previously occupied by a patient colonized or infected with a specific pathogen, then the new admission has an increased risk of acquiring the same organism [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…36,37,38 High compliance with the new disinfection protocol is likely to be sustained by the lack of procedural change needed in the case of CDI occurrence, the short disinfectant exposure time and the lack of unpleasant odour of the sporocide Oxygenon ® Liquid (Antiseptica). Our findings warrant the conclusion that using an oxygen-releasing sporicide for daily surface decontamination might be superior to targeted sporicidal disinfection in preventing nosocomial CDI.…”
Section: 25mentioning
confidence: 99%